Study habits and academic stress in students of a public educational institution in Puerto Maldonado - Estrada Araoz, Edwin Gustavo (2020)
The objective of the research was to determine the relationship between study habits and academic stress in students in the fifth grade of secondary education at a public educational institution in Puerto Maldonado. The approach was quantitative, the design was non-experimental and the correlational level. The sample was made up of 121 students, an amount that was determined by means of a probability sampling. The data collection instruments were the CASM-85 Study Habits Inventory, revision-2014 and the SISCO Inventory of Academic Stress. The results indicate that there is an inverse and significant relation between the study habits and the academic stress of the students since the Spearman's rho correlation coefficient was -0,365 with a p-value below the level of significance (p<0,05). It was concluded that adequate study habits of the students are related to low levels of academic stress.